Down syndrome from understanding the neurobiology to therapy - Dierssen, Mara; Torre, Rafael de la (Progress in brain research ;, 2012)
Down syndrome (DS) is the most common example of neurogenetic aneuploid disorder leading to mental retardation. In most cases, DS results from an extra copy of chromosome 21 (HSA21) producing deregulated gene expression in brain that gives raise to subnormal intellectual functioning. The topic of this volume is of broad interest for the neuroscience community, because it tackles the concept of neurogenomics, that is, how the genome as a whole contributes to a neurodevelopmental cognitive disorders, such as DS, and thus to the development, structure and function of the nervous system.